Ornamental plants associated with Buddhist figures in China - Xiaodan Xu; Chengmin Yan; Zhiying Ma; Qi Wang; Jie Zhao; Rui Zhang; Luyao He; Wei Zheng (BMC, 2023)
Abstract Background In China, many ornamental plants associated with Buddhist figures, including the Sakyamuni, Bodhisattva, and Arhat, were grown and worshiped because of their cultural and religious significance. However, the systematic collation and ethnobotanical information about these culturally important plants have yet to be fully understood. Methods Online information was collected from 93 e-commercial platforms for ornamental plants all over China. Field sampling was conducted in 16 ornamental markets and 163 Buddhist temples using key informant interviews and participatory observation with traders, tourists, and local disciples. The types, distributions, and associated characteristics of the screened plants were summarized and the evolving characteristics of these ornamental plants were analyzed. Results A total of 60 ornamental plants, including six varieties and one subspecies, were screened, of which 43 species were associated with Sakyamuni, 13 with Bodhisattva, and four with Arhat. Among the 60 species, three were regarded as the Asoka tree related to Buddha's birth, ten as the Bodhi tree connected to Buddha's enlightenment, three as the Sal tree associated with Buddha's nirvana, nine were related to Buddha's head, belly, or hand, and 18 were connected with Buddha as lotus throne, bamboo monastery, or Bodhi beads. The evolving characteristics of these ornamental plants primarily constituted the substitution of the original plants by similar native plant species, followed by the introduced species with comparable morphology to the Buddhist figures. Conclusions People grow ornamental plants associated with Buddhist figures to reflect their love and praise for plants and Buddha. The association between the ornamental plants and Buddhist figures will aid the inheritance of Buddhist culture and promote ornamental plants in the commercial market. Thus, the ethnobotany of ornamental plants associated with Buddhist figures can serve as a basis for future investigation of modern Buddhist culture.